Text Planner and Self-Assessment of Recount Writing Ability among Junior High School Students - Mafulah, Siti; Sribudiati, Wiwik; Haider, Sanwal (Universitas Islam Balitar, 2024)
This study aims to explore whether the use of text planner combined with self- assessment affects students' recount text writing ability at junior high school students. The research employed a pre-experimental method using a one-group pretest- posttest design. The participants were 32 students from class VIII-H of SMP Negeri 1 Turen. The results showed a significant improvement in the students' recount writing performance from pretest to posttest. The average score increased from 67.27 to 80.08, indicating that the intervention of using a text planner combined with self-assessment has a positive impact. The Paired Samples T-test further confirmed the statistical significance of this improvement, with a p-value of 0.000, which is less than the standard significance level of 0.05. These findings suggest that the use of a text planner to guide the organization of recount texts, combined with self-assessment to enable students to critically evaluate their own writing, can be an effective approach to improve junior high school students' recount writing ability. The study provides valuable insights for educators seeking to implement evidence- based strategies to support students' development in this genre of writing. In addition, due to the limitation of this study, it is reccommended for futrure researchers to conduct research on the different text type and the implementattion in the different level of students so that the use of text planner combined withh self-assessment can be generalized as an effective way to teach English Writing Skill.